The Basis of Legal Ijtihad in the Umayyah Period - Inas Setyaningtyas; Rara Intan Mutiara Fajrin; Nabila Riska S; Haidar Abdullah; Ratna Diyah Pamuji (Interdisciplinary Journal of Social Science and Education (IJSSE), 2024)
The work of the ulama in developing the study of Islamic law. can be seen from the many famous figures, including two of the four madzhab imams who became the center of knowledge from various Islamic regions at that time, and the contribution of the Umayyad government in bookkeeping and the spread of Islamic knowledge which has been written as one of the golden inks of history in Islam which influenced the rapid development of the knowledge of Islamic law at that time. In the early days of the Umayyad reign, several thought groups emerged which had a huge impact on contributing to the development of Islamic legal thought. which in the following journey turned into a theological school, such as the Khawarij which was a group that left the allegiance of the legitimate government at that time, the Sunnis, the majority of whom remained loyal to supporting the legitimate government, while the Shiites strengthened their existence in politics by developing their teachings and doctrines. These three schools contributed to the development of Islamic legal thought